Everyone to the concert (Journal of Parents and Teachers, 2026)
One of the most neglected aspects of our education system is music. Not only does the school neglect the cultivation of individual skills in learning to play a musical instrument, but it also pays virtually no attention to educating musical taste or developing an aesthetic appreciation of listening to music. Here we share the experience of La Coruña, where 11,000 local children attended the first cycle of School Concerts by the Galician Symphony Orchestra.
Keywords: music education, school concerts, Galician Symphony Orchestra